THE ANALYSIS OF THE ROLE OF ZAKAT ON THE POVERTY ALLEVIATION USING CIBEST MODEL (CASE STUDY OF RUMAH GEMILANG INDONESIA KAMPUS SURABAYA) - Dian Ghani Reza Dasangga; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Poverty is a condition in which a person cannot meet their basic needs. Zakat is one of the instruments in Islam to solve the problem of poverty. This research analyzes the poverty level of mustahik comparing the changes before and after the execution of a productive zakat program by taking a case study of Rumah Gemilang Indonesia Kampus Surabaya LAZ Al Azhar East Java. Respondents in this research are 31 mustahik with random sampling. The method of analysis used in this research is the CIBEST Model which consists of CIBEST quadrants and Islamic poverty index. CIBEST model attempts to analyze poverty from the material aspect as well as the spiritual aspect. The results of the study show that the productive zakat program can increase the revenue of mustahik and reduce the level of material poverty and absolute poverty. Keywords: CIBEST Model, Islamic poverty index, poverty, zakat produktifREFFERENCE Ayu Putri, Hurun Eka. (2018). Analisis kinerja BAZNAS Banyuwangi dengan pendekatan Indeks Zakat Nasional. Skripsi tidak diterbitkan. Surabaya: Universitas Airlangga.Bank Indonesia. (2016). Pengelolaan zakat yang efektif: Konsep dan praktik di berbagai Negara. Jakarta: Bank Indonesia.BAZNAS. (2019). Dampak zakat terhadap tingkat kesejahteraan mustahik (Studi kasus lembaga – lembaga program BAZNAS. Jakarta: BAZNAS.Badan Pusat Statistik Kota Surabaya. (2017). Profil kemiskinan di Kota Surabaya Tahun 2017. Surabaya: BPS.Badan Pusat Statistik Kota Surabaya. (2018). Profil kemiskinan di Kota Surabaya Tahun 2018. Surabaya: BPS.Beik, Irfan Syauqi & Laily Dwi Arsyianti. (2016).Measuring zakat impact on poverty and welfare using CIBEST model. Journal of Islamic Monetary Economics and Finance, 1(2), 141-160. DOI: https://doi.org/10.21098/jimf.v1i2.524Beik, Irfan Syauqi & Laily Dwi Arsyianti. (2015). Construction of CIBEST model as measurement poverty and welfare indices from Islamic perspective. Al-Iqtishad, 7(1), 87-104. DOI:10.15408/aiq.v7i1.1361Saputri, Henni Eka. (2017). Analisis dampak pendistribusian dana zakat, infak, sedekah dalam mengurangi kemiskinan (Studi kasus: Baitul Maal Masjid Jogokariyan Yogyakarta). Skripsi tidak diterbitkan. Bogor: Institut Pertanian Bogor.Pratama, Caesar. (2015). Pendayagunaan zakat produktif dalam mengurangi kemiskinan berdasarkan CIBEST model (Studi kasus: PT. Masyarakat Mandiri Dompet Dhuafa). Skripsi tidak diterbitkan. Bogor: Institut Pertanian Bogor._________. (2019). Profile Rumah Gemilang Indonesia [internet]. [diakses pada 10 November 2019]. Tersedia pada: http://rumahgemilang.com/profile-rumah-gemilang-indonesia/#page-content_________. (2015). Tsaqofi-Konsep Dasar Model CIBEST [internet]. [diakses pada 27 Oktober 2019]. https://www.republika.co.id/berita/koran/news-update/15/05/28/np23wg1-tsaqofi-konsep-dasar-model-cibest